الأسواق المالية الناشئة و الأسواق المتقدمة - بن ساحة, ياسمينة (My University, 2022)
Competition has intensified between advanced financial markets and emerging financial markets, especially emerging stock exchanges ,through which it highlighted the limited role of emerging stock exchanges with in their economies and the obstacles they face and limit their ability to grow and develop as their poor performance and their backwardness have become a matter that threatens their survival and continuation in light of the intense competition imposed on them by advanced stock exchanges, as integration between developed and emerging stock exchanges is one of the strategic options offers to emerging stock exchanges to raise their performance and their capabilities to face competition, and this study has attempted to identify the most Important stock market indicators that enable us to measure the efficiency of both emerging ( Brazil (and develop (USA)stock exchanges ,compare them and try to link them so that the process of linking exchanges does not become a mere technicalprocess that does not contribute to raising the volume Transactions in securities across borders between emerging and developed countries
Keywords: financial markets, emergingexchanges, advanced stock exchanges, indices, financial market efficiency